Análise das manifestações auditivas em individuos com hipertensão arterial sistêmica - Oliveira, Djanine Andrade (2014)
Objective: To determine the prevalence of auditory manifestations in individuals with hypertension and analyze the association between hearing loss, systemic hypertension and quality of life in hypertensive patients. Method: This was a prospective, observational, case-control study, carried out from June 2010 to December 2013 at the University Hospital Onofre Lopes, in Natal, Brazil, which involved 120 patients of both sexes were analyzed with a diagnosis of hypertension and 120 patients without a diagnosis of hypertension. The audiological function was assessed by tonal and vocal audiometry. The quality of life was defines by the MINICHAL BRASIL questionnaire. Results: The prevalence of hearing loss was high in both groups (82.5 % and 75.8 %, in hypertension group and control, respectively, p=0.003). The sensorineural was the most common type of hearing loss (48.5 %) in hypertension group while conductive hearing loss was predominant (61.5 %) in the control group. There were no difference in the intensity of hearing loss between the groups (p=0,21). The main hearing complaint was hearing loss (51 %), followed by ear pain (14 %). There was worse quality of life in hypertensive individuals with hearing loss (p= 0.0001). Conclusion: Hypertensive individuals showed higher prevalence of auditory events, including hearing loss, sensorineural hearing loss is predominant . Hearing loss is associated with worse quality of life of hypertensive individuals even when these pressure values are within normal limits